1996
DOI: 10.1046/j.1469-0705.1996.08040277.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional saline contrast hysterosonography and surface rendering of uterine cavity pathology

Abstract: A new technique that combines saline contrast hysterosonography with three-dimensional surface rendering for the visualization of uterine intracavitary pathologies is described. A total of 32 patients suspected of having uterine cavity pathologies on the basis of previous ultrasonography, hysterosalpingography or hysteroscopy were involved in the study. They were examined by three-dimensional high-frequency endovaginal probes (Combison 530, Kretztechnik, Zipf, Austria), with normal saline used as an expander a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…Recently, sonohysterography (SHG) with sterile saline solution has also been used as a diagnostic tool for uterine cavity assessment [9][10][11] but published data regarding its accuracy are based on a small series of patients [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sonohysterography (SHG) with sterile saline solution has also been used as a diagnostic tool for uterine cavity assessment [9][10][11] but published data regarding its accuracy are based on a small series of patients [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…17 Increasing experience with 3D sonography in combination with many favorable reports on SIS resulted in the introduction of 3D-SIS. [18][19][20][21][22][23] Although some studies concluded that more research is necessary for a final decision about the clinical relevance of 3D-SIS, 18,23 others reported excellent specificity and positive predictive values for 3D-SIS. [19][20][21] Therefore, 3D-SIS may be of clinical relevance because its use may increase the positive predictive value of SIS and may prevent women with a normal uterine cavity from undergoing diagnostic hysteroscopy.…”
mentioning
confidence: 99%
“…It was initially used for gynecologic and obstetric imaging; other applications in adults followed [1][2][3][4][5]. With the introduction of transducers that are useful in children, the first efforts have been undertaken to evaluate its potential in pediatric imaging [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%